Design, Simulation, and Implementation of a Dual-Layer Perforated Partially Reflective Surface for Gain and Bandwidth Enhancement of Dielectric Patch Antenna Arrays - Muftah Mohamed Asaadi; Khaled Mohamed Eshteiwi (African Journal of Advanced Pure and Applied Sciences, 2025)
The proposal, simulation, and experimental validation of a partially reflected surface applied over a high-density dielectric patch antenna array are presented. In order to improve the antenna bandwidth and gain, a partially reflective surface (PRS) is designed. By creating a positive reflection phase gradient with high reflectivity, these holey dielectric substrates are designed to enhance the antenna system’s electromagnetic performance. A partially reflective surface (PRS) made up of two thin, perforated dielectric substrates is used as a superstrate in the suggested design to increase the antenna’s gain and bandwidth. The effective permittivity of the dielectric superstrate is considerably altered by the addition of regularly spaced circular holes inside the PRS layers. The suggested arrangement makes use of smaller substrates, which helps to increase the operational bandwidth, in contrast to traditional designs, where the superstrate thickness usually equal to a quarter dielectric wavelength. A 3 dB gain bandwidth of 22% over the frequency range of 24.5 to 30.7 GHz was achieved. The antenna has a high simulated radiation efficiency of 92% along with a measured flat gain of roughly 16 dBi across this spectrum. Furthermore, the side lobe levels continue to be below -11 dB in the E-plane and -17 dB in the H-plane, demonstrating that unwanted radiation is effectively suppressed.